Synthesis and Evaluation of Thalidomide and Phthalimide Esters as Antitumor Agents. Issue 9 (18th June 2014) - Zahran, Magdy A. H.; Abdin, Yasmin G.; Osman, Amany M. A.; Gamal‐Eldeen, Amira M.; Talaat, Roba M.; Pedersen, Erik B.
<x xml:space="preserve">Abstract</x> A series of thalidomide and phthalimide ester analogs were efficiently synthesized from N‐chloromethylthalidomide, N‐chloromethylphthalimide, and N‐(2‐bromoethyl)phthalimide derivatives with various biologically important carboxylic acids. The synthesized compounds were purified and characterized by various chromatographic and spectroscopic techniques. The antitumor activity of all the synthesized compounds was screened against human liver and breast cancer cells, which showed that phthalimide ester 6a was the best cytotoxic compound against MCF7 cells, while all of the tested compounds showed a non‐cytotoxic effect against HepG2 cells. Compounds 5a, 6a, and 7a possess immunosuppressant effect, while compounds 5c, 5d, 6c, 6d, 7c, and 7d showed an immunostimmulatory effect. Meanwhile, estimation of the binding affinity for all the synthesized compounds toward the vascular endothelial growth factor receptor (VEGFR) showed that compounds 5a, 5b, and 7d were the most potent inhibitors.